Epididymal sperm reserve of indigenous pig of Meghalaya - Baishya, S K; Das, Anubrata; Khargharia, G; Naskar, S (The Indian Journal of Animal Sciences, 2007)
Growing indigenous pigs (36) of Meghalaya of 4 to 12 months of age were used to estimate the sperm reserve in caput, corpus and cauda epididymes. The testes and epididymides were removed from the boars by open method of castration and the epididymes were divided into caput, corpus and cauda regions on the basis of the external morphology. The sperm reserve of caput, corpus and cauda was estimated in filtrate by accuacell spectrophotometer after homogenizing each region of epididymes at 1500 rpm and filtering the homogenate. The distribution of sperm concentration in caput, corpus and cauda regions increased from 4 to 12 months of age and the corresponding sperm concentration were (x 109) 1.00±0.013 vs 5.342±0.110,0.765±0.021 vs 3.4±0.059, 4.243±0.121 vs 20.808±0.206 in caput, corpus and cauda respectively at 4 and 12 months of age. The sperm storage differed significantly (P&lt0.01) between regions of epididymes, being significantly (P&lt0.05) higher in cauda than in caput and corpus epididymes. The epididymal sperm reserve had a significant positive correlation with age (0.99), body weight (0.99), epididymal weight (0.97) and testes weight (0.98).